The Queue Distribution in Multiprocessor Systems with the Waiting Time Restriction - Sahakyan, Vladimir G.; Vardanyan, Artur P. (Mathematical Problems of Computer Science, 2021)
A queueing system model is considered, consisting of m (m ≥ 1) servicing devices and a maximum number of tasks with n (n ≥ 1) in the waiting queue. Each task is characterized by three random parameters (ν, β, ω), where ν is the number of servicing devices required to perform the task, β is the maximum time required to complete the task and ω is the possible time that the task can wait before assigning to run, after which it leaves the system without service. Tasks are accepted for service in the order of their entry into the system, i.e., FIFO (First-In-First-Out) discipline is used. In paper the equations are obtained for the state probabilities of the system in the stationary mode, which can serve as an assessment for real multiprocessor systems using MPI and OpenMP technologies.